Simple and Inexpensive Methods Development for Determination of Venlafaxine Hydrochloride from Its Solid Dosage Forms by Visible Spectrophotometry - K. Raghubabu; L. Shanti Swarup; B. Kalyanaramu; M. N. Rao; C. Ramdas (E-Journal of Chemistry)
Two simple, sensitive and cost effective visible spectrophotometric methods (M1 and M2) have been developed for the determination of venlafaxine hydrochloride from bulk and tablet dosage forms. The method M1 is based on the formation of green colored coordination complex by the drug with cobalt thiocyanate which is quantitatively extractable into nitro benzene with an absorption maximum of 626.4 nm. The method M2 involves internal salt formation of aconitic anhydride, dehydration product of citric acid [CIA] with acetic anhydride [Ac2O] to form colored chromogen with an absorption maximum of 561.2 nm. The calibration graph is linear over the concentration range of 10-50 µg/mL and 8-24 µg/mL for method M1 and M2 respectively. The proposed methods are applied to commercial available tablets and the results are statistically compared with those obtained by the reference method and validated by recovery studies. The results are found satisfactory and reproducible. These methods are applied successfully for the estimation of the venlafaxine hydrochloride in the presence of other ingredients that are usually present in dosage forms.